Beykoz Honor a Robust Online Exam Platform System - Elkhodary, Abdullah I.; Erkan , Feyza; Aburas , Abdurazzag A. (International Journal of Advanced Science Computing and Engineering, 2025)
In today’s digital landscape, online assessments have emerged as a pivotal element of educational systems worldwide. However, the rise of online examinations has also been accompanied by a troubling increase in cheating incidents. Research highlights that the most prevalent forms of online exam fraud include unauthorized access, screen sharing among students, and impersonation of test-takers. In response to these challenges, we introduce "Beykoz Honor," an innovative online exam platform meticulously engineered to incorporate a suite of advanced anti-cheating features. This platform employs multi-factor authentication (MFA) to ensure that only legitimate users can access assessments. Additionally, a browser lockdown mechanism restricts navigation away from the exam interface, while IP and device tracking enable monitoring of candidates to prevent fraudulent activity. Furthermore, question randomization adds another layer of integrity by altering the order and selection of exam questions for each student. Research has consistently shown that these comprehensive measures significantly mitigate the risks associated with academic dishonesty. This paper examines the architecture of the Beykoz Honor system, outlines its phased implementation strategy, and conducts a thorough market analysis with a particular focus on Turkish universities. Looking toward the future, we discuss ambitious plans to integrate artificial intelligence to detect irregularities during assessments. Real-time monitoring solutions are also on the horizon, adding yet another dimension to the platform's capability to uphold academic integrity. These innovations represent ongoing efforts to enhance the efficacy and reliability of online examinations, ensuring a fair and equitable assessment environment for all students.